A Stripe Review of Natural Resources Management Research in the CGIAR - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
The NRM Research Stripe Review, for which the ISPC developed the Executive Summary on the basis of the Panel’s inputs, seeks to identify conceptual and operational issues that still require attention from CRP leaders, CGIAR Centers, and CGIAR leadership, in order to develop research that will meet CGIAR system level outcomes.